Apoferritin applications in nanomedicine - Heger, Zbynek; Skalickova, Sylvie; Zitka, Ondrej; Adam, Vojtech; Kizek, Rene (Nanomedicine (London, England), 2014)
Nanomedicine as a continuously evolving discipline is still looking for a structure with perfect properties that is usable as a multifunctional transporter. Great potential is attributed to synthetic materials such as fullerenes, porous hollow silica nanoparticles and single-wall nanotubes, among others. However, materials that are natural to the human body are more acceptable by the organism, and thus become an attractive approach in this field of research. Ferritins are proteins that naturally occur in most living organisms throughout evolution and may be a possible transporter choice. Numerous applications have demonstrated the possibilities of iron-free ferritins, called apoferritins, serving as platforms for various nanomedical purposes This article summarizes the advantages and disadvantages of these proteins and discusses their practical applications and future perspectives.
Keywords: Nanomedicine; apoferritiny; genetická terapie; nanotrasporter; magnetic resonance imaging; Drug Carriers; lidé; Biosensing Techniques; therapeutic agents; nanoscale; Protein Conformation; horse spleen ferritin; photodynamic therapy; self-assembly; nanomedicína; biosenzitivní techniky; konformace proteinů; nosiče léků; Apoferritins; Genetic Therapy; Humans